Corrosion behavior of candidate heat exchanger materials in oxidizing and reducing gases relevant to oxyfuel power plants. (4th May 2018) - Huczkowski, P.; Najima, S.; Chyrkin, A.; Grüner, D.; Quadakkers, W. J.
Abstract: In the present paper, the oxidation behavior of potentially suitable construction materials for heat exchanging components in coal fired power plants was studied in the temperature range 550–700 °C. The selected materials (low alloy steel 13CrMo44, martensitic steel P92, austenitic steel S304HCu and Ni-base alloy 617) were exposed in a simulated atmosphere typical for oxyfuel combustion and the results were compared with the behavior in a test gas simulating oxyfuel gas with addition of CO, thus simulating locally occurring reducing operating conditions which may happen due to incomplete combustion. The oxidation/corrosion behavior was studied by gravimetry in combination with a number of characterization methods such as optical microscopy, scanning electron microscopy with energy dispersive X-ray analysis (SEM/EDX) and glow discharge optical emission spectroscopy (GDOES). For the low alloy steel and P92 only minor differences in oxidation rates between the different environments were found. For S304HCu generally smaller corrosion rates were found in the reducing gas, whereas for alloy 617 the effect of gas composition depended on temperature. The obtained results are interpreted on the basis of thermodynamic considerations comparing equilibrium activities of the main species in the gas atmospheres with the thermodynamic stabilities of various possible corrosion products.